An empirical examination of repeated auctions for biodiversity conservation contracts - Groth, Markus (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2008)
The European Union’s Council Regulation on support for rural development by the European Agricultural Fund for Rural Development has introduced auctioning as a new instrument for granting agri-environmental payments and awarding conservation contracts for the recent multi-annual budgetary plan. This paper therefore deals with the conception and results of two case study auctions for conservation contracts. Results of two field experiments show much differentiated bid prices in the model-region and budgetary cost-effectiveness gains of up to 21% in the first auction and up to 36% in the repeated auction. Besides these promising results, some critical aspects as well as lessons to be learned will also be discussed in this paper to improve the design and performance of upcoming conservation auctions.
Keywords: Environmental Policy; Ecosystem; Service Provision; Biodiversity; Umweltpolitik; Biodiversität; Auktion; 330 Wirtschaft